Building counter-archives: Oral history programmes of the Sinomlando Centre and Memory Work in Africa and the South African History Archive. (June 2022) - Bhebhe, Sindiso; Ngoepe, Mpho
Counter-archives, including those aligned to universities, have grown and developed as alternatives to the conventional and traditional mainstream archives. The purpose of this paper is to look into how such counter-archives are building and using their holdings. The study is based on two purposively selected counter-archives, which are the Sinomlando Centre and Memory Work in Africa and South African History Archive. The data were collected through interviews and document analysis, especially of the respective websites. One of the conclusions drawn from the paper is that counter-archives are here to stay as the general public is losing confidence in established traditional institutions.